2018
DOI: 10.1063/1.5033967
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the retention performance of an ultra-thin HfO2 resistance switching layer in an integrated memory device

Abstract: The retention behavior of a HfO2 resistive switching memory device with a diameter of 28 nm and an ultra-thin (1 nm) HfO2 layer as the switching layer was examined. Ta and TiN served as the oxygen vacancy (VO) supplying the top and inert bottom electrodes, respectively. Unlike the retention failure phenomenon reported in other thicker oxide-based resistance switching memory devices, the current of both the low and high resistance states suddenly increased at a certain time, causing retention failure. Through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…In the OFF state of the FTO/PMMA/Ag and FTO/PMMA+oxadiazole/Ag device, the ohmic conduction was observed in a low voltage region, and the slope increased to over 2 (2.94, 1.19, and 3.78), manifesting that the space-charge-limited conduction (SCLC) among the disconnected portion of the conducting filament governs in a high voltage region. These conduction properties in ON and OFF states are also in keeping with those in the previous report [40][41][42].…”
Section: Resultssupporting
confidence: 91%
“…In the OFF state of the FTO/PMMA/Ag and FTO/PMMA+oxadiazole/Ag device, the ohmic conduction was observed in a low voltage region, and the slope increased to over 2 (2.94, 1.19, and 3.78), manifesting that the space-charge-limited conduction (SCLC) among the disconnected portion of the conducting filament governs in a high voltage region. These conduction properties in ON and OFF states are also in keeping with those in the previous report [40][41][42].…”
Section: Resultssupporting
confidence: 91%
“…Many memristors and ReRAM memories were reported to fail at temperatures above 80 °C due to repeated formation and/or deletion of CFs mainly composed of oxygen vacancies. Their assistance in generating an insulating oxide layer of random nature trigger thermal instabilities of CFs [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the erratic behavior of the following cycles, it may be alleged that irreversible filaments are gradually formed after 1000 cycles inducing a certain device instability. This process is typically related to the diffusion of oxygen vacancies into the CF deletion region [ 46 ]. A certain material fatigue allows the memristor to reform during its lifetime.…”
Section: Resultsmentioning
confidence: 99%
“… 16 , 17 , 34 However, the memristors failed after 10 5 cycles during consecutive writing, which was previously explained by the sudden diffusion of O vacancies into CFs increasing the conductance of HRS. 41 …”
mentioning
confidence: 99%
“…Previous studies confirmed that a sudden diffusion of O vacancies into the CF ruptured region during the switching repetition may decrease the HRS values and cause device failure. 41 Hence, the random nature of CFs growth may increase the probability of such detrimental events and thus must be avoided. Controlled O vacancies generation is a critical factor in switching uniformity and reproducibility.…”
mentioning
confidence: 99%